2000
DOI: 10.1007/s004210000264
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related elevations in venous pH with citrate ingestion do not alter 40-km cycling time-trial performance

Abstract: The purpose of the current investigation was to determine whether sodium citrate enhances endurance cycling performance and, if so, what dosage(s) produces this effect. Eight trained [peak power output: 362 (48) W; power:weight: 5.1 (0.4) W x kg(-1), mean (SD)] male cyclists were requested to complete four, 40-km time-trials, each separated by 3-7 days, on their own bicycles, mounted on a Kingcycle ergometer. To mimic the stochastic nature of cycle road races, the time-trials included four 500-m, four 1-km and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Indeed in a previous study employing shorter 40-km time trials, which also included repeated HIE, we (39) found that sprinting performance fell progressively as did blood lactate concentrations, whereas pH rose, the opposite of the predicted effect if fatigue is regulated by peripheral metabolites.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Indeed in a previous study employing shorter 40-km time trials, which also included repeated HIE, we (39) found that sprinting performance fell progressively as did blood lactate concentrations, whereas pH rose, the opposite of the predicted effect if fatigue is regulated by peripheral metabolites.…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, the noteworthy feature of this and other studies (33,36,37,39) is the reproducibility of the pacing strategies used by subjects during closed trials of the type used in this study. This invites the question of the nature of the internal physiological cues that determine such a response, since the subjects in all our trials receive no external cues other than the distance covered.…”
Section: Discussionmentioning
confidence: 76%
“…13 14 More probably, a developing metabolic acidosis may induce a progressively increasing homoeostatic respiratory compensation, which increases the perception of discomfort, at the same time producing a compensatory alkalosis. 16 This escalating discomfort ultimately causes the conscious decision to terminate the exercise bout. 15 Furthermore, skeletal muscle ATP concentrations are never reduced to less than 50% of the resting value under all conditions of exercise, including maximal exercise in persons with a reduced capacity to generate ATP either oxidatively or glycolytically, or in muscles rendered ischaemic by the application of a tourniquet and forced to contract until exhaustion by external stimulation.…”
Section: Fatigue and Whole Body Homoeostasismentioning
confidence: 99%
“…However, the gastrointestinal (GI) acceptance profile of sodium bicarbonate is narrow and 10% of humans cannot adequately tolerate the doses needed to elicit an ergogenic effect [6,9]. Thus, ingesting sodium bicarbonate in high enough doses to induce an adequate modification of the acid–base balance during exercise can be detrimental to performance [6,9,10]. Sodium citrate (Na-CIT) is another alkalizing agent that has been studied in sports over a broad array of doses, times and distances but the results on its ergogenic effect have been inconclusive [2-4,10-14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ingesting sodium bicarbonate in high enough doses to induce an adequate modification of the acid–base balance during exercise can be detrimental to performance [6,9,10]. Sodium citrate (Na-CIT) is another alkalizing agent that has been studied in sports over a broad array of doses, times and distances but the results on its ergogenic effect have been inconclusive [2-4,10-14]. Indeed, the meta-analysis by Carr et al [8] reported an unclear effect on performance (0.0 ± 1.3%) for a 60 sec maximal effort, with a dose of 0.5 g kg -1 .…”
Section: Introductionmentioning
confidence: 99%